Peran Program Inkubasi Terhadap Pengelolaan Keuangan Pada Tenan Binaan Ibti Maleo Techno Center - Umi Hainik; Juliana Kadang; Anisah Anisah; Muslimin Muslimin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the role of the Incubation Program in Financial Management for Tenants Assisted by the IBTI Maleo Techno Center. The incubation program here plays a very important role in understanding the financial management process of IBTI-assisted tenants, namely Local Accountants. This research is a descriptive qualitative study that shows the role of IBTI in running the financial incubation program as well as in assisting financial management for local chartered accountants. This research uses observation data collection methods and interview on Local Accountant tenants. The data analysis used is in the form of data collection, data reduction, data presentation, and drawing conclusions. The financial management process consists or is measured from four basic frameworks for business financial management, these four basic frameworks consist of budget planning, financial recording, financial reporting and financial control. Overall, the Incubation program plays a very important role in developing the financial management capabilities of tenants assisted by IBTI Maleo Techno Center, which can also increase the chances of success and sustainability of their business in the future.